THE TEACHING OF SPEAKING BY USING WEBTOON AT CHOICE ENGLISH COURSE PARE KEDIRI - Adlim, Moh. Syaiful (Jurnal Pendidikan Bahasa Inggris Proficiency, 2019)
Webtoon is a type of digital comic or comic application. The research aimed to find out the teaching of speaking by using Webtoon at Choice English course Pare Kediri. The design used is descriptive qualitative. The data collection method were interview, observation, documentation, questionnaire and filed note. The result of this research showed that the teaching of speaking by using Webtoon at Choice English course Pare Kediri had been supported by curriculum but it had not been documented, it also had been supported by syllabus and lesson plan, the material was from Webtoon, and the techniques used were retelling story and role play. The evaluation of this program was taken on Saturday at the last week by calling the students one by one to deliver a speech based on the tittle they took in the lottery. The students’ response was known that students were very active, happy and they enjoyed the program. The result of the students’ after getting this program was there were 8 (40 %) students got A (Excellent), 11 (55 %) students that B (Very Good), 1 (5 %) student got C (Good), and no student got C (Average) or D (Poor).